A PERCEPÇÃO DE PROFESSORES QUANTO AO ENSINO DE UMA ESTUDANTE SURDA EM UM CURSO DE FORMAÇÃO DE DOCENTES - Gonçalves Arantes Gennari, Ana Paula; Leite, Sandra Rodrigues; Herbella do Prado Talhetti, Giselle; Blanco, Marília Bazan; Negrão de Araújo, Roberta; Luccas, Simone (Faculdade de Filosofia e Ciências, 2019)
School inclusion asserts the fulfillment of everyone's right to education. That said, the following question emerged. In what way has the teaching of a deaf student occurred in a teacher training course? This, in turn, determined the general objective of this research: to analyze the perceptions of teachers of a teacher training course regarding the teaching process of a deaf student. For that, a qualitative investigation was carried out and the instrument of data collection was an online questionnaire. The analysis of the results was based on the assumptions of the Discursive Textual Analysis. With this, it was evidenced that the majority of the participants defined the inclusion process as a welcome opportunity. Regarding difficulties, most admitted that they feel when working with students with special needs, because they do not have a command of the Brazilian Sign Language or do not have adequate material and need to adapt contents and assessments. However, a minority claimed to have no difficulties, because classes are taught through differentiated strategies, so that everyone has a chance to learn. In addition, it was found that there is no standardization of teaching methods. Among the actions indicated are: text adaptation; individualized service; visual activities; videos with subtitles; creation of activities. Finally, it is suggested that teacher training should include in its curriculum theoretical and methodological knowledge that provides a teaching action that meets the needs of any student.